Juridical Analysis Of The Settlement Of Disputes Over Multiple Ownership Of Land Assets Of The Army In Indonesia - SULAIMAN; Angga Busra Lesmana (Jurnal Hukum Volkgeist, 2024)
This research analyzes the resolution of multiple ownership disputes over Army asset land, which is often a source of agrarian conflict in Indonesia. By using the juridical-empirical method, which combines normative legal analysis with practical observations in the field. Statute Approach and case approach. This research aims to identify the factors causing the emergence of two certificates on one land parcel issued by the National Land Agency, as well as its legal impact. The results show that economic factors, abuse of position, and inappropriate land use are the main causes. Legal consequences include legal uncertainty, economic loss, and certificate cancellation. The research recommends resolution through mediation, consultation and more effective litigation mechanisms to ensure justice and legal certainty.